SARS -infectious disease of 21st century (Faculty of Medicine Universitas Indonesia, 2005)
Severe acute respiratory syndrome (SARS) is an emerging viral infectious disease. According to the World Health Organization, a suspected case of SARS is defined as documented fever (temperature >38°C), lower respiratory tract symptoms, and contact with a person believed to have had SARS or history of travel to an area of documented transmission. A probable case is a suspected case with chest radiographic findings of pneumonia, acute respiratory distress syndrome (ARDS), or an unexplained respiratory illness resulting in death, with autopsy findings of ARDS without identifiable cause. In this article some SARS epidemiological data in Indonesia will also presented. There are 7 SARS suspected cases and 2 probable cases were registered in Indonesia on the period of 1 March to 9 July 2003, and no more cases were reported after that time. How will be SARS progression in the future will be a subject of discussion among scientist, and we will have to wait and be prepared for any development might occur. (Med J Indones 2005; 14: 59-63) Keywords: SARS, Case Definition, Etiology, Indonesia